0.08(y + -1) + 0.12y = 0.14 + -0.05(10)
Reorder the terms:
0.08(-1 + y) + 0.12y = 0.14 + -0.05(10)
(-1 * 0.08 + y * 0.08) + 0.12y = 0.14 + -0.05(10)
(-0.08 + 0.08y) + 0.12y = 0.14 + -0.05(10)
Combine like terms: 0.08y + 0.12y = 0.2y
-0.08 + 0.2y = 0.14 + -0.05(10)
Multiply -0.05 * 10
-0.08 + 0.2y = 0.14 + -0.5
Combine like terms: 0.14 + -0.5 = -0.36
-0.08 + 0.2y = -0.36
Solving
-0.08 + 0.2y = -0.36
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '0.08' to each side of the equation.
-0.08 + 0.08 + 0.2y = -0.36 + 0.08
Combine like terms: -0.08 + 0.08 = 0.00
0.00 + 0.2y = -0.36 + 0.08
0.2y = -0.36 + 0.08
Combine like terms: -0.36 + 0.08 = -0.28
0.2y = -0.28
Divide each side by '0.2'.
y = -1.4
Simplifying
y = -1.4